Continuing medical and dental education on the global stage: the nexus of supporting international Christian healthcare workers and developing educators - Lyubov D Slashcheva; Mark A Strand; Ruth E VanReken; Collin Sanford; J Dwight Phillips; Gloria Halverson (Health for All Nations, 2016)
One of the challenges facing international healthcare missionaries is that of maintaining up-to-date knowledge and staying current with professional certification. Since 1978, annual programs by the Christian Medical and Dental Associations have offered professional continuing education to thousands of US healthcare professionals serving as missionaries in the regions of Africa, Asia, and, in more recent years, globally. In addition, conference programming is designed to prepare, train, and support healthcare missionaries to, in turn, serve as educators in their places of ministry. The program is designed for both professional education and personal encouragement. Utilizing historical documents from program facilitation and interviews from those involved with its implementation, this paper describes the history, vision, and favorable quantitative growth and qualitative impact on participants. The program continues to grow as healthcare missionaries are educated near their places of service, while reinforcing their own roles as educators.